Efficiency of National early warning score (NEWS) for early detection of sepsis in a community hospital - Wongtida, Chinoros (Journal of Primary Care and Family Medicine (PCFM), 2020)
Title: Efficiency of National early warning score (NEWS) for early detection of sepsis in community hospital Main investigator: CHINOROS WONGTIDA, MD Work location: Serm Ngam Hospital Background: Sepsis is a serious problem in Thailand. As a previous study, Many Analytical tools have been developed for finding and evaluating patients who have sepsis. National early warning score “NEWS” has been mentioned to be the most accurate tools. However, Serm Ngam Hospital has never used this screening tool for evaluating patients with sepsis. Therefore, it is the reason of this study. Objective: To study the prevalence of patients with suspected sepsis by applying national early warning score (NEWS) and to study the relationship between the incidence of death in patients with suspected sepsis and national early warning score (NEWS). Method: The retrospective descriptive study of 115 people who were treated with sepsis in Serm Ngam Hospital, Lampang Province, from October 2017 to July 2019. The data were collected from medical records and “NEWS” were calculated via the NEWS & SEPSIS screening program. After that these data were analyzed by descriptive statistics and the relationship factors were analyzed by Chi square for independent test. Result: There were 115 patients participated in this study. The prevalence of sepsis patients had a NEWS score greater than or equal to 5 or higher, or being in the "think sepsis" of 93 cases (80.9%) (95% CI. 7.39-8.68, p <.01) from this study, there was a statistically significant relationship between the level of clinical risk according to national early warning score (NEWS) and incidence of death (OR 2.895, 95% CI 1.070-7.827, p .032) but there was no statistically significant relationship between the level of clinical risk according to national early warning score (NEWS) and septic shock (OR 1.336, 95% CI. 625-2.856, p .454) Conclusion: The national early warning score (NEWS) can be used to early detect patients who suspected sepsis without laboratory tests and can be used to predict the incidence of death from sepsis.